2014
DOI: 10.1021/jp412112g
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Induced Phase Transition in Hydrogen-Bonded Supramolecular Structure: Ammonium Formate

Abstract: High-pressure behaviors of hydrogen-bonded supramolecular structure, ammonium formate (NH4 +COOH–, AF), have been investigated under pressure by in situ synchrotron X-ray diffraction (XRD) and Raman spectroscopy up to 20 GPa. Under ambient conditions, AF exhibits three-dimensional hydrogen-bonded networks with two molecules crystallize in a monoclinic unit cell of space group Pc. A structural phase transition can be identified at around 1.8 GPa, as indicated by the abrupt changes in Raman spectra as well as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…However, still there are lots of fundamental aspects to be unearthed as to how speci c changes are enforced in materials with respect to their crystallographic structural features at high-pressure and high-temperature conditions [1][2][3][4][5]. Moreover, some of the materials show stable crystallographic con guration even at a considerably high pressure of GPa range [6,7] whereas a few materials undergo reversible [8][9][10][11] and irreversible [12,13] phase transitions during pressure compression and decompression. Hence, it has become increasingly ubiquitous prospect for researchers to understand better the basic concepts of structural phase transition of materials under external stimuli conditions [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, still there are lots of fundamental aspects to be unearthed as to how speci c changes are enforced in materials with respect to their crystallographic structural features at high-pressure and high-temperature conditions [1][2][3][4][5]. Moreover, some of the materials show stable crystallographic con guration even at a considerably high pressure of GPa range [6,7] whereas a few materials undergo reversible [8][9][10][11] and irreversible [12,13] phase transitions during pressure compression and decompression. Hence, it has become increasingly ubiquitous prospect for researchers to understand better the basic concepts of structural phase transition of materials under external stimuli conditions [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In the perspective of crystallographic structural phase transitions, reversible and irreversible phase transitions are the focal point such that the concepts behind the phenomena occurring in materials at high-pressure and high-temperature ought to be explored. Surprisingly, the concept of the reversible phase transitions with respect to pressure and temperature is by and large remaining in the dark that is to be brought to light since identi ed highly e cient switchable materials are very less than that of irreversible materials [8][9][10][11]. Scarcity of switchable phase transition materials have kept numerous industrial emergency applications on wait such as molecular switches, resistive memories, phase lters, transmitters, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Bennett et al have demonstrated the crystal–amorphous reversible phase transitions in a zeolitic imidazolate framework at pressure compression and decompression stages . Zou and his team have performed the static-high-pressure experiment and reported the reversible crystallographic phase transition for ammonium formate, lithium amide, acetamide, and magnesium silicide (Mg 2 Si) …”
Section: Introductionmentioning
confidence: 99%
“…One-dimensional (1D) tubular channels have been utilized for ion and molecular transport, where coupled Na + -K + ionic transport has been observed in biological molecular assemblies. Because the 1D transport system has both directionality and anisotropy, artificial ionic channels have attracted much attention for the fabrication of passive and gated ionic transport systems. A large number of synthetic approaches have been reported for the fabrication of artificial 1D channels based on amphiphilic, polymeric, and macrocyclic molecules with hydrogen bonding and van der Waals interactions. Simple and well-known low-molecular-weight van der Waals crystals of tris­( o -phenylenedioxy)­cyclotriphosphazene (TPP) derivatives have been reported to form 1D channels, where weak van der Waals interactions form 1D channels in the close-packing crystal structure. Because the energies of van der Waals interactions are quite low, around 1–2 kJ mol –1 , van der Waals molecular assemblies are easily dissociated by external stimuli such as heat and ultrasonic energy . In contrast, hydrogen bonds have energies ranging from 5 to 20 kJ mol –1 , allowing controlled association–dissociation processes of molecular assemblies using external stimuli. For example, hydrogen bonds in complementary base pairs in DNA and the secondary structures of proteins play an important role in the fabrication of biological molecular assemblies, and controllable hydrogen-bonding interactions have been utilized for repair and reconstruction of molecular assembly structures. …”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of hydrogen-bonding interaction energies is suitable for a reversible structural transformation driven by external factors such as temperature, pressure, and molecular adsorption. Although hydrogen-bonded host–guest complexes of 1 with AcOH have been identified in the 1D channel, other guest molecules with a variety of sizes, shapes, and intermolecular interactions have not been examined from the viewpoint of the structural diversity for hydrogen-bonding network structures. Herein, we tried to fabricate the 1 ·(guest) complexes with various guest molecules: dichloroacetic acid (Cl 2 AcOH), pyrrole (Pyrr), pyridine (Py), and 3,4-difluoroaniline (F 2 Ani), 1,2-diaminoethane (EDA), 1,3-diaminopropane (ProDA), 1,5-diaminopentane (PenDA), and 1,7-diaminoheptane (HepDA) (Scheme ).…”
Section: Introductionmentioning
confidence: 99%